Metabolic profiling analysis of root exudates from the Cd hyperaccumulator Sedum alfredii under different Cd exposure concentrations and times. Issue 9 (7th May 2015) - Luo, Qing; Sun, Li-na; Wang, Hui; Hu, Xiao-min
<x xml:space="preserve">Abstract</x> The variation of root exudates from the Cd hyperaccumulator Sedum alfredii under different Cd exposure concentrations and times was researched.